A hero's return - Nichols, Carrie (Harlequin special edition, 2025)
Years of military service taught decorated veteran Braden Sullivan how to be strong. It didn't teach him how to be vulnerable. Back in his Oregon hometown, with a job as a helicopter pilot and a two-family home to renovate, he's not at all prepared for his heart to take flight after meeting his tenant, Cassie Donovan. The widowed single mom is beautiful, charming...and terrified of loving another pilot after losing her husband in a crash. Overcoming her fears and his own uncertainties will take courage--but isn't that what a hero soldier is for?